MICRO AND NANO-ELECTROMECHANICAL SYSTEMS (BIO-MEMS/NEMS) FOR BIOMEDICAL APPLICATIONS - Sok, Vanna; Kiri, Ming; Dara, Ravi (Journal of Biomedical and Techno Nanomaterials, 2026)
Micro and nano-electromechanical systems (Bio-MEMS/NEMS) have emerged as pivotal technologies in the biomedical field, offering the potential for precise diagnostics, targeted drug delivery, and real-time monitoring of biological systems. These systems integrate mechanical, electrical, and biological components at micro- and nanoscale levels, enabling the development of highly sensitive, compact devices. Despite their promise, challenges related to material selection, biocompatibility, and scalability remain critical barriers to their widespread adoption in medical applications. The aim of this study is to explore the potential of Bio-MEMS/NEMS for various biomedical applications, including disease diagnosis, therapeutic interventions, and health monitoring. The research focuses on evaluating the performance, functionality, and biocompatibility of these systems in clinical environments. A systematic review of existing literature and case studies was conducted, focusing on Bio-MEMS/NEMS technologies used in diagnostic devices, biosensors, and drug delivery systems. Experimental data from in vitro and in vivo studies were analyzed to assess device performance and safety. The findings highlight the remarkable capabilities of Bio-MEMS/NEMS, particularly in terms of sensitivity, precision, and integration with biological systems. However, challenges such as biofouling, tissue integration, and long-term stability remain unresolved. Bio-MEMS/NEMS present significant opportunities for advancing medical technologies, but further research is necessary to overcome existing limitations and ensure the safe and effective application of these systems in clinical practice.